Plasma homocysteine and total antioxidant status in diabetic chronic kidney disease and diabetic renal allograft recipients: effect of folic acid therapy - Wadwa, Pooja C.; Sandhu, Jashan; Sandhu, Jasvinder S.; Avasthi, Gurcharan L.; Bajwa, Navjot; Sohal, P. M. (International Journal of Clinical Trials, 2015)
Background: Indian population is usually deficient in folic acid. Aim was to study the plasma homocysteine and antioxidant status in type 2 diabetics and healthy individuals before and after folate therapy. Methods: This study was done in four groups of 25 cases each. These included: type 2 diabetics with end stage diabetic chronic kidney disease (CKD) (group A); diabetic renal allograft recipients with normal and stable graft function (group B); uncomplicated type 2 diabetics (group C); and age and sex matched healthy controls (group D). The serum homocysteine and total antioxidant status (TAS) were measured at baseline and after 4 weeks of folate therapy. Results: The plasma homocysteine levels were 18.163.80, 16.150.66, 12.480.82 and 23.361.61 mol/L in group A, B, C and D respectively. The homocysteine levels were significantly low in all diabetic groups when compared to healthy controls. The plasma homocysteine were significantly elevated in stage 5 diabetic CKD and diabetic renal transplant recipients as compared to uncomplicated diabetics. After four weeks of folate therapy, there was a significant decrease of homocysteine in all the groups. The mean values of TAS were 1.42 0.18, 1.49 0.18, 1.17 0.06 and 1.60 0.86 pg/ml in group A, B, C and D respectively. There was no significant correlation between diabetic groups and healthy controls. No change was observed in TAS levels after folate therapy. Conclusions: Our results show significant hyperhomocysteinemia in healthy Indians. Plasma homocysteine were significantly low in all diabetic groups as compared to healthy individuals. We suggest supplementation of Indian diet with folic acid.